Flood Disaster Preparedness and Response in Zimbabwe: A Case Study of Tsholotsho District, Zimbabwe - Nobuhle Sibanda; Mark Matsa (IGI Global, 2023)
Effective disaster risk reduction entails enhancing disaster preparedness for effective response and to “Build Back Better” in recovery, rehabilitation, and reconstruction. This paper sought to analyse Tsholotsho district's preparedness for flood disaster and recovery. A local government self-assessment tool with key questions and measurements against the 10 essentials for making cities resilient was used to solicit information from every stakeholder of the district civil protection. The district has a risk management plan but not a contingency one. Though the district's hazard monitoring system lags behind, the early warning system, propelled by telecommunications, leadership, and NGOs, is quite effective. This paper recommends that climate change scenarios be considered and included in the district's contingency plan and that a disaster risk policy should be formed which recognises disaster preparedness as an issue of governance and performance. The CPU should make disaster preparedness a culture and a conscious practice and encourage communities to practise disaster preparedness.